The Impact of Cognitive Functioning on Daily Occupations for People with Multiple Sclerosis: A Qualitative Study - Aoife Mc Auliffe; Sinéad M. Hynes (Scholarworks @ WMU, 2019)
Background: Cognitive rehabilitation research in multiple sclerosis is ever-developing, but the impact of cognitive difficulties, seen in 40% to 80% of people, on daily occupations is not well known. The aim of this study is to explore the needs of people with MS who have self-reported cognitive deficits. Methods: An exploratory qualitative descriptive research design was used. Data was collected through semi-structured telephone interviews with the participants. Recordings were transcribed and analyzed thematically. Results: Seven participants were recruited (mean age 47). Three themes were developed through associations found in the data. "Neglected symptom" reported the participants' frustrations around the importance afforded to cognition by health care providers. "Impact on participation in daily occupations" described the everyday impacts of cognitive difficulties. "Adaptations and adjustments to continued participation" reported how the participants manage, despite their difficulties. Conclusion: The findings describe how cognitive difficulties affect individuals with multiple sclerosis and their occupations, as well as the dissatisfaction felt with the progress in and access to cognitive treatment and research. The results indicate the need for occupation-focused interventions in cognition for people with multiple sclerosis that address daily challenges.